The effect of seminal fluid on TBx2 and TBX3 expression and activity in cervical cancer cells - Cooper, George William (Division of Medical Biochemistry and Structural Biology, 2017)
Cervical cancer is one of the most common female cancers in Africa, both in terms of incidence and mortality, and is disproportionately prevalent in developing nations due to a lack of adequate access to healthcare. While new vaccine technologies are rapidly reducing the incidence of Human Papilloma Virus (HPV) infection, the primary causative agent of cervical cancer, new cases continue to accumulate in the developing world. Beyond the role of HPV in the early stages of cancer development, the molecular aetiology of this disease is poorly understood. Frequent exposure to seminal fluid (SF), the liquid component of semen, has been proposed as a potential driver of oncogenesis in cervical cancers and has been shown to exacerbate some aspects of cervical cancers. While some of the cellular signaling pathways responsible for these phenomena have been identified, much remains to be elucidated. We hypothesized that TBX2 and TBX3, two highly homologous transcription factors frequently implicated in other cancers, may be responsible for mediating some of the effects of SF on cervical cancer cells. We established that TBX3 protein is significantly overexpressed in both primary cervical adenocarcinomas and squamous cell carcinomas compared to normal tissue. SF was shown to increase expression of both TBX2 and TBX3 mRNA in HeLa and CaSki, but not C-33 A, cervical cancer cell lines. Furthermore, SF upregulated TBX3 protein expression in both of these cell lines. In contrast, TBX2 protein was undetectable in these cell lines. In addition, our results showed that SF treatment of HeLa cells increases the expression of the known TBX3 target gene, p21CIP1/WAF1 (p21), while having no effect on PTEN expression. Transient knockdown of TBX3 resulted in decreased p21 expression in SF-treated cells suggesting that SF upregulation of p21 is dependent on TBX3. This is the first study to investigate TBX3 protein expression in primary cervical tissues and SF regulation of TBX3. However, further research is required in order to elucidate the role of SF-induced TBX3 in cervical cancer development. The identification of the role of TBX3 in cervical cancer development could aid in the development of more effective treatments for cervical cancers and could potentially impact sexual health policy recommendations for women with cervical cancer.